Evaluation of the Bioequivalence and Pharmacokinetics of Two Tablet Formulations of Isosorbide-5-mononitrate after Single Oral Administration in Healthy Volunteers - Niopas, Ioannis; Daftsios, Athanasios C.; Nikolaidis, Nicolaos (Arzneimittelforschung, 2002)
The pharmacokinetic parameters of two oral formulations of 20 mg tablets of isosorbide-5-mononitrate (CAS 16051-77-7, Dilavenil® as test and another commercially available preparation as reference) were compared in an open-label, randomized, single oral dose, two-period cross-over design in 20 healthy volunteers under fasting conditions. Plasma concentrations of isosorbide-5-mononitrate were measured by a validated gas chromatographic assay. The parametric 90 % confidence intervals of the geometric mean values of the test/reference ratios were 101.2 % to 108.5 % (point estimate: 104.7 %) for AUC0–∞, 101.6 % to 110.7 % (point estimate: 106.2 %) for AUC0–t, and 98.1 % to 115.5 % (point estimate: 106.1 %) for Cmax, within the acceptance criteria for bioequivalence (80 %-125 %). Tmax values were analyzed by the nonparametric Wilcoxon test and the difference was not statistically significant. Therefore, it is concluded that the test and reference isosorbide-5-mononitrate formulations are bioequivalent for both the extent and the rate of absorption.
Keywords: CAS 16051-77-7; Dilavenil®; Isosorbide-5-mononitrate, bioavailability, bioequivalence, clinical pharmacokinetics; tablet formulations